2017
DOI: 10.1128/aem.02783-16
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmotic Agents and Antibiotics Affect Dissolved Oxygen and pH Concentration Gradients in Staphylococcus aureus Biofilms

Abstract: Biofilms on wound surfaces are treated topically with hyperosmotic agents, such as medical-grade honey and cadexomer iodine; in some cases, these treatments are combined with antibiotics. Tissue repair requires oxygen, and a low pH is conducive to oxygen release from red blood cells and epithelialization. We investigated the variation of dissolved oxygen concentration and pH with biofilm depth and the variation in oxygen consumption rates when biofilms are challenged with medical-grade honey or cadexomer iodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 85 publications
3
16
0
Order By: Relevance
“…The concentration used in the present study of 50 µg/mL, in the middle of this range, was found to inhibit planktonic growth completely (data not shown) but was insufficient to generate even a single log reduction in viable cell counts. These results are consistent with and enrich the long-standing observations in vitro and in vivo that aggressive antibiotic treatment of mature biofilms is often insufficient to eradicate bacterial respiration, [37][38][39] even in cases where viable cell counts are affected, and that following cessation of antimicrobial therapy biofilms often regrow. [40][41][42] Traditional investigations of biofilm oxygen usage are typically conducted on steady-state biofilms wherein oxygen penetration no longer changes with time, and studies examining the effect of antibiotic administration often infer continued oxygen utilization by identifying anoxic conditions at the biofilm base or by probing the 1D oxygen profile, with the exact response of the oxygen sink to antibiotic challenge unknown.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The concentration used in the present study of 50 µg/mL, in the middle of this range, was found to inhibit planktonic growth completely (data not shown) but was insufficient to generate even a single log reduction in viable cell counts. These results are consistent with and enrich the long-standing observations in vitro and in vivo that aggressive antibiotic treatment of mature biofilms is often insufficient to eradicate bacterial respiration, [37][38][39] even in cases where viable cell counts are affected, and that following cessation of antimicrobial therapy biofilms often regrow. [40][41][42] Traditional investigations of biofilm oxygen usage are typically conducted on steady-state biofilms wherein oxygen penetration no longer changes with time, and studies examining the effect of antibiotic administration often infer continued oxygen utilization by identifying anoxic conditions at the biofilm base or by probing the 1D oxygen profile, with the exact response of the oxygen sink to antibiotic challenge unknown.…”
Section: Discussionsupporting
confidence: 89%
“…The concentration used in the present study of 50 µg/mL, in the middle of this range, was found to inhibit planktonic growth completely (data not shown) but was insufficient to generate even a single log reduction in viable cell counts. These results are consistent with and enrich the long‐standing observations in vitro and in vivo that aggressive antibiotic treatment of mature biofilms is often insufficient to eradicate bacterial respiration, even in cases where viable cell counts are affected, and that following cessation of antimicrobial therapy biofilms often regrow …”
Section: Discussionsupporting
confidence: 89%
“…Generalizations can be made concerning the direction of a concentration gradient for metabolic products and substrates based on Reaction-Diffusion theory [4]. For example, metabolic products produced by the biofilm, such as carbon dioxide and acids, can quickly diffuse at the biofilm-fluid interface but do so at a slower rate in the interior [4,14]. Conversely, the availability of metabolic substrates, such as glucose, oxygen, and other nutrients, are generally greatest at the fluid-biofilm interface and are slowly depleted as they diffuse towards the center of the biofilm [14,15].…”
Section: Bacterial Growthmentioning
confidence: 99%
“…For example, metabolic products produced by the biofilm, such as carbon dioxide and acids, can quickly diffuse at the biofilm-fluid interface but do so at a slower rate in the interior [4,14]. Conversely, the availability of metabolic substrates, such as glucose, oxygen, and other nutrients, are generally greatest at the fluid-biofilm interface and are slowly depleted as they diffuse towards the center of the biofilm [14,15]. It also follows that the ability of antibiotics to penetrate a biofilm and reach an effective concentration is dependent on diffusion [14].…”
Section: Bacterial Growthmentioning
confidence: 99%
See 1 more Smart Citation